Assessment of the Expansion of Sugar Cane:: Application of the Sustainability Barometer in the municipalities of Barretos and Jaboticabal, São Paulo State, Brazil (Sustainability in Debate, 2014)
With the premise of reducing emissions of greenhouse gases, international interest in biofuelshas grown considerably in recent years. With the increasing demand and consequent expansion,the need to assess the impacts on the environment and society is unquestioned. Brazil, with largeareas of arable and large current production of sugarcane, in addition to the added knowledgefrom decades of research and production of bioethanol, has the potential for expansion, but theconsequences should be considered alongside to increased economic returns. For this, theapplication of the Barometer of Sustainability was made for two municipalities in the state of SãoPaulo: one with strong sugarcane expansion (Barretos), and another with stagnant production(Jaboticabal). The main objective was to identify the impacts based on the comparison ofmunicipalities and identify causality in relation to the expansion of the culture under study. Theapplication of sustainability barometer indicates a negative impact in the municipality withsugarcane expansion. In addition, the municipality without sugarcane expansion improves itshuman welfare performance against a stabilization of the municipality with expansion, indicatinga relationship between the expansion of sugarcane and precariousness of human development.